Facility management technology : lessons from the U.S. and Japan - Teicholz, Eric.; Ikeda, Takehiko (New York : Wiley, 1995)
This book will help facility managers establish their own total systems concept.
Includes bibliographical references (p. 173-175) and index.
aia 10/05/13
Loans
Keywords: Facility management - data processing; Automation; Factory management